Language Politeness in Student and Teacher Interaction of EFL Classroom (Universitas Negeri Semarang, 2022)
In this article, we discuss about language politeness, focusing in the form of verbal politeness. A language that contains elements of verbal politeness is the main purpose of this study, as well as the art and strategy of verbal politeness used by students. This type of survey is a qualitative descriptive survey. The object this study is exploring the importance of Language Politeness. From the research, there are several words as the data result of the student speeches. The data collection techniques used in this study were tapping, recording, and note-taking techniques. The data analysis techniques use the interactive model of Miles and Huberman. The data trustworthiness is validated by doing memberchecking to avoid the bias of the researcher. The results found data that contained 4 kinds of principles of language politeness for teachers and students in the EFL Classroom which consisted of wisdom maxim 1 data, consensus maxim 1 data, appreciation maxim 2 data.